2015
DOI: 10.2989/16085914.2015.1019827
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of effluent from the de-oiling works of a decommissioned Nigerian crude oil pipeline usingPalaemonetes africanus

Abstract: Oil industry activities often involve the cleaning and replacement of pipelines, usually resulting in the discharge of effluents into waterbodies. The toxicity of de-oiling effluent from a decommissioned crude oil pipeline in the Niger Delta region of Nigeria was assessed using the brackish water shrimp Palaemonetes africanus in a 96 h laboratory bioassay. On the basis of the computed 96 h LC 50 , the effluent showed a significant dose-dependent relationship in its toxicity between 24 and 96 h of exposure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The same trend have been reported by (15,21,22). The concentration of the Crude oil able to kill fifty percent (50%) of the Paleamonetes africanus within 96 hrs (96hrs LC50), NOEC, LOEC, and TUa was calculated using methods stipulated in (13).…”
Section: Pateamonetes Africanussupporting
confidence: 66%
“…The same trend have been reported by (15,21,22). The concentration of the Crude oil able to kill fifty percent (50%) of the Paleamonetes africanus within 96 hrs (96hrs LC50), NOEC, LOEC, and TUa was calculated using methods stipulated in (13).…”
Section: Pateamonetes Africanussupporting
confidence: 66%
“…For example, Agbalagba et al (2013) evaluated the concentrations of Naturally Occurring Radioactive Materials (NORM) substances such as 226 Ra, 228 Ra and 40 K in drinking water samples from three oil and gas producing communities, and found that concentrations are well above the WHO permissible limits. In a 96-hour lab bioassay conducted on brackish water shrimps, Amaeze et al (2015) assessed the toxicity of de-oiling effluents from a decommissioned oil pipeline facility in the Niger Delta while Asagbra et al (2015) found polycyclic aromatic hydrocarbons (PAHs) in water, sediment and tissue of tilapia fish in the Warri River at Ubeji. Interestingly, surface and groundwater pollution from oil pipelines and other facilities including leaks from aging, dilapidated and abandoned infrastructure; and those from transport and localised refining of stolen oil in Ogoniland was the focus of Linden and Palsson (2013).…”
Section: Research Gapmentioning
confidence: 99%